2019
DOI: 10.1177/1077546319890747
|View full text |Cite
|
Sign up to set email alerts
|

A research of sliding mode control method with disturbance observer combining skyhook model for active suspension systems

Abstract: Based on a nonlinear two-degree-of-freedom model of active suspension systems, an approach of the sliding mode control with disturbance observer combining skyhook model sliding mode control with disturbance observer combining is proposed for improving the performance of active suspension systems, and the effectiveness of the proposed approach is validated by the active suspension system plant. Two problems of active suspension systems are solved by using the proposed approach when the tire is excited by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Based on the new lead-lag correction controller, this paper proposed a two zeros and three poles lead-lag correction controller as shown in equation (19). The main difference between H twoÀpoles and H threeÀpoles is in the high frequency band, the attenuation effect of the three-pole controller is more obvious.…”
Section: Stability Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the new lead-lag correction controller, this paper proposed a two zeros and three poles lead-lag correction controller as shown in equation (19). The main difference between H twoÀpoles and H threeÀpoles is in the high frequency band, the attenuation effect of the three-pole controller is more obvious.…”
Section: Stability Controller Designmentioning
confidence: 99%
“…The frequency-response method is popular primarily because it has the advantages of convenient operation, intuitive effect, and robustness. 15,16 Indeed, there are also many advanced control algorithms, such as sliding-mode control [17][18][19] and fuzzy control, 20,21 and these algorithms are demonstrated to be effective. However, the experiment results indicate that the chattering problem caused by the sliding mode control may increase the torque oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…This specific type of excitation consists of multiple frequency components, which is usually used to investigate the performance of suspension system. 1,17 Figure 4(a) and (b) shows the displacement of road excitation in time domain and frequency domain, respectively. It can be found that the excitation frequency is mainly in the 0–5 Hz frequency range.…”
Section: An Equivalent 2-dof Modelmentioning
confidence: 99%
“…The riding comfort and the maneuverability of vehicle are two important considerations in the design of suspension systems of modern cars. [1][2][3][4][5] The riding comfort is provided by isolating the car body from road, and the maneuverability is obtained by keeping the tireroad gripping. Since the stiffness and the damping in passive suspension systems are not adjustable, it is difficult to balance the conflict between the riding comfort and the maneuverability at various road excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to deal with system uncertainties, and to enhance the robustness of the system, they combined the sliding mode control (SMC) with backstepping controller. Owing to its robustness against uncertainties and its simple design, SMC has become very popular as a robust controller for uncertain systems [23][24][25][26][27][28]. The main goal of using an SMC is to control a system which is subjected to uncertainties and disturbances.…”
Section: Introductionmentioning
confidence: 99%